The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1111/j.1476-5381.1978.tb07008.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Guanethidine Blockade of Sympathetic Nerve Terminals by Tetraethylammonium and 4‐aminopyridine

Abstract: 1 The effect of tetraethylammonium (TEA) and 4-aminopyridine (4-AP) on the inhibitory effect of guanethidine on noradrenaline (NA) release was investigated in the perfused spleen of the cat. 2 Guanethidine blocked the release of NA evoked by nerve stimulation. TEA and 4-AP readily reversed this inhibitory effect, and the NA output was nearly doubled after repeated stimulation of the nerves. On subsequent perfusion with Krebs solution without TEA or 4-AP, the inhibitory effect of guanethidine reappeared. 3 The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…A third possibility is that guanidine allows greater than normal amounts of calcium to accumulate inside the sympathetic nerve terminals during an action potential to reverse guanethidine blockade of NA release. TEA and 4-AP have also been shown to reverse guanethidine blockade (Kirpekar et al, 1978). Since all three agents are known to enhance the calcium concentration in the nerve terminals (Lundh et al, 1977), and since little is known regarding their ability to open the sodium channels which have been blocked by a local anaesthetic, we would like to suggest that antagonism between guanidine and guanethidine probably involves mobilization by guanidine of calcium within the sympathetic nerve terminals.…”
Section: Effect Of Graded Concentrations Of Guanidine On Noradrenalinmentioning
confidence: 99%
See 1 more Smart Citation
“…A third possibility is that guanidine allows greater than normal amounts of calcium to accumulate inside the sympathetic nerve terminals during an action potential to reverse guanethidine blockade of NA release. TEA and 4-AP have also been shown to reverse guanethidine blockade (Kirpekar et al, 1978). Since all three agents are known to enhance the calcium concentration in the nerve terminals (Lundh et al, 1977), and since little is known regarding their ability to open the sodium channels which have been blocked by a local anaesthetic, we would like to suggest that antagonism between guanidine and guanethidine probably involves mobilization by guanidine of calcium within the sympathetic nerve terminals.…”
Section: Effect Of Graded Concentrations Of Guanidine On Noradrenalinmentioning
confidence: 99%
“…An alternative suggestion is that guanethidine or bretylium may depress NA release by blocking the increase in calcium permeability associated with evoked release (Kirpekar, Wakade, Dixon & Prat, 1969;Krauss, Carpenter & Kopin, 1970;Kirpekar et al, 1978). Since the effect of guanidine appears to be related in some way to intraneuronal calcium concentration, it was of interest to determine whether guanidine, like TEA and 4-AP (Kirpekar et al, 1978), would reverse the guanethidine blockade of sympathetic nerves. Figure 6 shows that guanidine reversed the inhibition of NA release by guanethidine during nerve stimulation at 10 Hz.…”
Section: Effect Of Graded Concentrations Of Guanidine On Noradrenalinmentioning
confidence: 99%
“…These observations suggest that antagonism of the tracheal relaxant actions of KCOs is a property shared by several agents classically described (Louis & Howes, 1990) as adrenergic neurone blocking agents. The ability of the adrenergic neurone blocking agents selectively to inhibit the airways smooth muscle relaxant actions of the KCOs without antagonizing agonists at P-adrenoceptors or alkylxanthines is shared both by sulphonylureas such as glibenclamide (Murray et al, 1989;Black et al, 1990;Nielsen-Kudsk et al, 1990;Berry et al, 1991;Raeburn & Brown, 1991) and by phentoamine (Murray et al, 1989;McPherson & Angus, 1990 Kirpekar et al (1978) observed that the K+-channel inhibitors tetraethylammonium (TEA) and 4-aminopyridine (4-AP) could reverse the ability of guanethidine to inhibit the neural release of noradrenaline in the in situ perfused spleen of the cat. Stutzin et al (1983) observed that the K+-channel inhibitor, apamin, could antagonize guanethidine in inhibiting contractile responses to the electrical stimulation of nerves in the guinea-pig isolated vas deferens.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments with apamin and tetraethylammonium also sug gest that an increase in potassium conduc tance inducing hyperpolarization of the vas cular smooth muscle cells is probably not the mechanism underlying the relaxation. Te traethylammonium enhances transmitter re lease [47,48] even in calcium-dependent nerves which release transmitter indepen dently from sodium channels [32,33] in the canine coronary artery, tetraethylammoni um did not enhance the relaxation to elec trical stimulation.…”
Section: Discussionmentioning
confidence: 99%